Occurrence and Morphology of MB2 Canals in Maxillary First Molars in an Indian Subpopulation: A Cone Beam Computed Tomography Study - Shetty, Aditya; Bhat, Raksha; Babu, Bessy; Hegde, Mithra N.; Shetty, Chitharanjan; Shetty, Preethesh; Latha Senthilkumar, Priyanka (Journal of Health and Allied Sciences NU, 2021)
Introduction Molars have been known to display varied morphologies. Maxillary first molar is the tooth with the largest volume and most complex root and root canal anatomy; also, possibly the most treated and least understood posterior tooth. The present study aimed to investigate the occurrence and morphology of MB2 canals in maxillary first molars in an Indian subpopulation (Dakshina kannada) using cone beam CT (CBCT) imaging.Materials and Methods A total of 330 maxillary molars were placed on “U-” shaped modelling wax template, mimicking the natural arch and digitally scanned, of which 196 scans met the inclusion criteria and were analyzed for unusual root canal anatomy by CBCT. To analyze the occurrence and morphology of the canals, the acquired data was examined by two endodontists and discussed till an agreement was reached.Results The results were subjected to descriptive analysis. The majority of patients 103 (52.6%) teeth showed the presence of MB2 canals. As much as 83.5% of teeth depicted Vertucci's type II morphology, and 16.5% teeth presented with Vertucci's type IV morphology.Conclusion CBCT overcomes the limitations of conventional radiography. However, the decision to use CBCT in the management of endodontic problems must be based on a case-by-case basis and only when sufficient diagnostic information is not obtained from diagnostic tests.
Keywords: CBCT; MB2 canals; root canal morphology; 3D imaging; maxillary molars